b - Kaku, Michio & Thompson, Jennifer; Thompson, Jennifer (b, 1995)
Beyond Einstein takes readers on an exciting excursion into the discoveries that have led scientists to the brightest new prospect in theoretical physics today -- superstring theory. What is superstring theory and why is it important? This revolutionary breakthrough may well be the fulfillment of Albert Einstein's lifelong dream of a Theory of Everything, uniting the laws of physics into a single description explaining all the known forces in the universe
Includes bibliographical references (p. [211]-212) and index.
Keywords: Unified field theories; Superstring theories; Supersymmetry; Cosmology